Management Analysis of Research and Development Costs - Dennis Rumanov (GoAcademica Research & Publishing, 2021)
The study discusses the techniques of management analysis of research and development expenditures. It determinesthe features of the costsat the early stages of the product life cycle, discloses goals and objectives of the analysis, the analysis techniquesof budget costs in the context of responsibility centers, separate projects and cost items. The factors and the evaluation of their impact on the amount of costs are identified.